2013
DOI: 10.1155/2013/740201
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of FXYD-3 Is Involved in the Tumorigenesis and Development of Esophageal Squamous Cell Carcinoma

Abstract: Objective. To investigate the association of FXYD-3 expression with clinicopathological variables and PINCH in patients with ESCC. Patients and Methods. Expression of FXYD-3 protein was immunohistochemically examined in normal esophageal mucous (n = 20) and ESCC (n = 64). Results. Expression of FXYD-3 in the cytoplasm markedly increased from normal esophageal epithelial cells to primary ESCC (P = 0.001). The expression of FXYD-3 was correlated with TNM stages and depth of tumor invasion. Furthermore, the cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…FXYD5 is a transmembrane auxiliary subunit of the Na + -K + -ATPase; it shows a 2.5-fold increase in glioblastoma. No direct link with glioblastoma has been reported to date, however it has been found up-regulated in adamantinomatous craniopharyngiomas in children [ 57 ] and other members of the FXYD family are known to be associated with different cancer types such as urothelial carcinoma [ 58 ], esophageal squamous cell carcinoma [ 59 ] and cholangiocarcinoma [ 60 ]. FXYD channels are involved in the anti-oxidative stress in vascular smooth muscle, thus controlling the vascular tone [ 61 ] and blood pressure [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…FXYD5 is a transmembrane auxiliary subunit of the Na + -K + -ATPase; it shows a 2.5-fold increase in glioblastoma. No direct link with glioblastoma has been reported to date, however it has been found up-regulated in adamantinomatous craniopharyngiomas in children [ 57 ] and other members of the FXYD family are known to be associated with different cancer types such as urothelial carcinoma [ 58 ], esophageal squamous cell carcinoma [ 59 ] and cholangiocarcinoma [ 60 ]. FXYD channels are involved in the anti-oxidative stress in vascular smooth muscle, thus controlling the vascular tone [ 61 ] and blood pressure [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FXYD genes encode for proteins that function to regulate the transport functions of N a+ /K + ATPases in a variety of normal cell systems (Crambert et al 2005 ; Yamamoto et al 2009 ). One member of this family, FXYD3, not only serves to regulate ATPase function in normal physiological systems, but several studies have shown that overexpression of this member of the FXYD family is associated with a number of cancers, and has been implicated in direct action in the formation of at least one type of cancer (Yamamoto et al 2009 ; Li et al 2014 ; Zhu et al 2013 ; Grzmil et al 2004 ). While increased expression of FXYD3 has been associated with breast cancer, the factors that promote up-regulation of this protein in mammary cells have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…FXYD3 protein is expressed in a number of cells in normal, untransformed tissues, including the bladder, lung, stomach and skin, but has been reported to be highly overexpressed in many tumors such as breast, androgen-dependent prostate, pancreatic, and colon cancer (Yamamoto et al 2009 ; Li et al 2014 ). Overexpression of FXYD3 is also believed to be involved in the tumorigenesis and development of esophageal squamous cell carcinoma (Zhu et al 2013 ). Although increased expression of FXYD3 is associated with various cancers, the relevant biological factors and their associated mechanisms of actions through which FXYD3 is increased in transforming and cancer cell systems have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have reported that FXYD3 is expressed in numerous types of cancer. FXYD3 expression was initially described in breast cancer ( 7 ), and subsequently detected in prostate cancer, CRC, pancreatic cancer and ESCC, in which FXYD3 was reported to be significantly upregulated in tumor tissues compared with normal adjacent mucosal tissues ( 11 17 ). However, in lung cancer and glioma, FXYD3 was demonstrated to be expressed at low levels compared with healthy paracancerous tissues ( 18 – 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…FXYD3 is expressed in numerous healthy tissues, including the uterus, stomach, colon and skin ( 9 , 10 ). However, FXYD3 expression has also been identified in various types of cancer, including breast cancer ( 7 ), prostate cancer ( 11 , 12 ), colorectal cancer (CRC) ( 13 ), pancreatic cancer ( 14 – 16 ), esophageal squamous carcinoma (ESCC) ( 17 ), lung cancer ( 18 , 19 ) and glioma ( 20 ). Furthermore, FXYD3 was demonstrated to be associated with the clinical prognoses of these types of cancer.…”
Section: Introductionmentioning
confidence: 99%